(untitled) - Hanzo, Lajos (Hoboken, NJ, 2007)
Video Compression and Communications has been updated and condensed yet remains all-encompassing, giving a comprehensive overview of the subject. Covering compression issues, coding delay, implementational complexity and bitrate, the book also looks at the historical perspective to video communication. New edition of successful and informative text, Wireless Video Communications; Substantial new material has been added on areas such as H.264, MPEG4 coding and transceivers; Clear presentation and broad scope make it essential for anyone interested in wireless communications; Systematically converts the lessons of Shannon's information theory into design principles applicable to practical wireless systems. This book is ideal for postgraduates and researchers in communication systems but will also be a valuable reference to undergraduates, development and systems engineers of video compression applications as well as industrialists, managers and visual communications practitioners
Keywords: Video compression,Digital video,Mobile communication systems,Hệ thống truyền thông di động,Kỹ thuật nén hình ảnh